GDRP AND INFLATION AS PREDICTORS FOR PROFITABILITY RATIOS (A CASE STUDY FOR LOCAL GOVERNMENTS IN INDONESIA) - Kuntaryanto, Oki (KIAT BISNIS, 2013)
After the fall of Soehartoâs regime, Indonesia begins to endorse reformation on every sector. Oneof the important thing is to eradicate the country from corruption. Corruption can be prevented byendorsing a system, which encourage transparency and accountability. By the issuance ofGovernment Rule No. 24 Year 2005 about Governmental Accounting, the transparency andaccountability are facilitated within the rule. This research tries to investigate the influence ofGDRP and inflation on profitability of local governments in Indonesia. This research isexploratory in nature due to the rareness of similiar researches. This research employs data fromlocal governmentsâ audited financial statements in Indonesia. By using judgmental sampling,financial statements which the opinions are disclaimer and adverse are excluded from the analysis.The data analysis then conducted using ordinary least square. This research finds that both GDRPand inflation have influence on profitability ratios. For the future researches, the finding from thisresearch can be extended using other ratios.Keywords: GDRP, Inflation, Local Governments, Profitability Ratio